Exploring Climate Change Problem-Solving Skills Among Junior High Students: An Empirical Analysis from Madura - Nabilah, Hasna; Hariyono, Eko; Suprapto, Nadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to explore the problem-solving skills of junior high school students in Madura in relation to climate change issues. Understanding these skills is crucial for preparing students to tackle environmental challenges effectively.Methodology A descriptive quantitative approach was employed, collecting data from 63 students through a set of problem-solving skill indicators. The indicators measured various aspects of students' abilities to understand, devise plans, carry out those plans, and reflect on their solutions to climate-related problems. The results indicate that 73% of students fall into the low category of problem-solving skills, while only 27% demonstrate moderate skills. Notably, no students achieved high or very high ratings. Specific analysis revealed that students exhibited a moderate understanding of problems but showed low performance in devising plans, executing those plans, and reflecting on their outcomes. These findings highlight significant gaps in students' problem-solving capabilities concerning climate change. The low proficiency across various indicators suggests a need for enhanced educational strategies to develop these essential skills. The analysis indicates that without targeted interventions, students may struggle to effectively address the complexities of climate issues.